Large-Scale Screening and Identification of Novel Pathogenic Staphylococcus aureus Genes Using a Silkworm Infection Model. (8th January 2020) - Paudel, Atmika; Hamamoto, Hiroshi; Panthee, Suresh; Matsumoto, Yasuhiko; Sekimizu, Kazuhisa
Abstract: The regulatory network of virulence factors produced by the opportunistic pathogen Staphylococcus aureus is unclear and the functions of many uncharacterized genes in its genome remain to be elucidated. In this study, we screened 380 genes whose function was unassigned, utilizing gene-disrupted transposon mutants of the community-acquired methicillin-resistant S. aureus USA300 for pathogenicity in silkworms. We identified 10 strains with reduced silkworm killing ability. Among them, 8 displayed reduced virulence in a mouse model as evidenced by reduced colony-forming units in organs of infected mice. The role of each gene in pathogenicity was further confirmed by complementation and pathogenicity tests in silkworms, where we found that the phenotype was not restored in 1 strain. Additionally, some of the mutants displayed reduced hemolysis, proteolysis, pigment production, and survival in murine RAW 264.7 monocyte-macrophage cells. These newly identified genes involved in virulence will enhance our understanding of the pathogenicity of S. aureus . Abstract : We performed a large-scale screening of gene-disrupted mutants of Staphylococcus aureus using a silkworm infection model and identified 8 novel genes involved in the aggravation of virulence in both silkworm and mouse models.